Thematic Learning Strategy of Teacher to Slow Learners in Inclusive Elementary School - Melyana Fitri, Rila; Sumaryanto, Totok; Rifa’i RC3, Achmad (Educational Management, 2019)
The purpose of this study is: to describe the teacher's strategy in developing thematic learning media for students with special needs, slow learner; to describe the implementation of thematic learning models in slow learner students; to describe the implementation of thematic learning assessment in slow learner students. This study uses a case study qualitative approach. The source of the data is from the teacher who teaches the slow leaner students, while the data regarding the strategies used by the teacher was obtained from some information with interview techniques, observation and documentation studies. The validity of the data is by triangulation of data sources and methods. The results of this study are as follows: the teacher's strategy in compiling thematic learning media in slow learner students is the same as regular students namely referring to the 2013 Curriculum; the implementation of thematic learning models in slow learner students in principle is the same as regular students by applying various learning models but for slow learner students there is special assistance; and the assessment of thematic learning in slow learner students is the same as regular students covering aspects of attitudes, knowledge and skills.